Seaweed copper ammonia non-woven fabric and preparation method thereof

Through the preparation method of modified seaweed fibers and cuproamino fibers, the interface bond strength between the fibers is enhanced, and the problem of deformation of existing mask non-woven fabrics when pulled is solved, achieving uniform distribution of mask essence substances and good absorption effect.

CN119465507APending Publication Date: 2025-02-18SHANGHAI JISUO IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411636136.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The interface bonding strength between existing seaweed fibers and cuproamino fibers is weak, which causes the non-woven fabric of the mask to easily deform when pulled, affecting the uniform distribution of the essence of the mask and the absorption effect of the human facial skin.

Method used

Through the preparation method of modified seaweed fibers and modified cuproamino fibers, the glutaraldehyde and calcium chloride solution are cross-linked, and further modified is combined with cellulose nanocrystals and silk fibroin solutions to enhance the interfacial binding strength between the fibers. .

Benefits of technology

Modified seaweed cuproamino non-woven fabric is not easy to separate and misalign when pulled, ensuring the uniform distribution of the essence of the mask and good absorption effect, improving the overall use effect of the mask product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of mask non-woven fabric materials, and particularly discloses a seaweed copper ammonia non-woven fabric and a preparation method thereof. The seaweed copper ammonia non-woven fabric is prepared from the following raw materials in parts by weight: 18-25 parts of modified seaweed fibers; 75 to 85 parts of modified copper ammonia fiber; in the preparation of the modified alginate fiber, glutaraldehyde is firstly used as a cross-linking agent, and hydroxyl and carboxyl in the molecular structure of the alginate fiber are used as cross-linking points, so that calcium ions and most self-chain segments of the alginate fiber form a cross-linked network structure, and at the moment, the surface characteristics of the alginate fiber are also changed; and treating by using a cellulose nanocrystal solution to obtain the cellulose nanocrystal. In the preparation of the modified copper ammonia fiber, the copper ammonia fiber is firstly subjected to pressure modification, so that the microstructure of the copper ammonia fiber is changed; and modifying the surface of the pretreated copper ammonia fiber by using a silk fibroin solution. The seaweed copper ammonia non-woven fabric disclosed by the invention can show better anti-pulling performance, so that mask essence substances carried by the seaweed copper ammonia non-woven fabric can uniformly act on facial skin of a human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of facial mask non-woven fabric materials, and more specifically, to a seaweed copper-ammonia non-woven fabric and a preparation method thereof. Background Art

[0002] Non-woven fabric, also known as nonwovens, non-woven fabric, and non-woven fabric, is made of directional or randomly arranged fibers through friction, adhesion, bonding or a combination of these methods; non-woven fabric is a common carrier of facial mask essence substances, with a large carrying capacity and a soft and comfortable application feel. The popular non-woven masks on the market are mostly blended non-woven fabrics with a thickness of 30g-70g.

[0003] In the selection of raw materials for non-woven fabric manufacturing, seaweed fiber has good biocompatibility and biodegradability, and strong air permeability and hygroscopicity, so that it can fully absorb essence during use and maintain the water-locking, moisturizing and breathable properties of facial mask products; cuprammonia fiber can quickly absorb and release moisture, and has a powerful bactericidal effect, which can inhibit the growth of a variety of pathogens and bacteria; therefore, seaweed fiber and cuprammonia fiber are usually mixed on the market to obtain facial mask non-woven fabrics with the above functions.

[0004] With regard to the above-mentioned related technologies, the inventors believe that, in the process of carrying the mask essence, in order to ensure that the mask non-woven fabric fully fits the user's facial skin, it will inevitably be pulled by the user. Since the interface bonding strength between the seaweed fiber and the cuprammonia fiber is relatively weak, it is easy to deform after being pulled. Although there is not much change in the macroscopic naked eye, from the microscopic structure, a sparse and dense distribution state has been formed, which causes uneven distribution of the mask essence. It is difficult for the human facial skin to evenly absorb and utilize the mask essence. Over time, it will cause differences in nourishment in different areas of the user's facial skin, which will ultimately affect the overall use effect of the mask product.

[0005] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention

[0006] In order to improve the interfacial bonding strength between seaweed fiber and cuprammonia fiber so that the facial mask nonwoven fabric exhibits excellent tensile resistance, the present application provides a seaweed cuprammonia nonwoven fabric and a preparation method thereof.

[0007] In the first aspect, the present application provides a seaweed copper-ammonia nonwoven fabric, which adopts the following technical solution: A seaweed copper-ammonia non-woven fabric is made from the following raw materials in parts by weight: 18-25 parts of modified seaweed fiber; 75-85 parts of modified cuprammonia fiber; The modified seaweed fiber is prepared by the following steps: S1, soaking the seaweed fiber in a 5-10% calcium chloride solution, adding a 6-8% glutaraldehyde solution for cross-linking, the cross-linking temperature is 30-50° C., the time is 2-4 hours, taking out the seaweed fiber, washing and drying it, and obtaining the pretreated seaweed fiber; S2, placing microcrystalline cellulose in deionized water for acid hydrolysis to obtain a cellulose nanocrystal solution with a mass fraction of 2-5%, soaking the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treating at 20-30° C. for 40-60 min, then taking out, washing and drying to obtain modified seaweed fiber; The modified cuprammonia fiber is prepared by the following steps: S1, placing the cuprammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 7-8Mpa, and treating it for 3-5min to obtain pretreated cuprammonia fiber; S2. Soak the pretreated cuprammonium fiber obtained in step S1 in a silk fibroin solution with a concentration of 45-55 mg / ml for 1-3 hours, take it out and dry it to obtain modified cuprammonium fiber.

[0008] By adopting the above technical scheme, in the preparation of modified seaweed fiber, glutaraldehyde is first used as a crosslinking agent, and the hydroxyl and carboxyl groups in the molecular structure of the seaweed fiber are used as crosslinking points, so that calcium ions and most of the self-chain segments of the seaweed fiber form a crosslinked network structure, and the surface properties of the seaweed fiber are also changed; then, cellulose nanocrystal solution is used for treatment, so that cellulose nanocrystals are associated on the surface of the pretreated seaweed fiber, forming a connecting bridge between the macromolecules of the seaweed fiber, and inhibiting the relative slip between the macromolecular chains. In the preparation of modified copper-ammonia fiber, the copper-ammonia fiber is first pressure-modified to change its own microstructure; and then the surface of the pretreated copper-ammonia fiber is modified with a silk protein solution. The modified seaweed fiber and modified cuprammonia fiber not only have excellent structural strength, but also when the modified seaweed fiber and modified cuprammonia fiber are used together to prepare seaweed cuprammonia non-woven fabric, the two can show better interface bonding strength. When pulled, they are not easy to separate or dislocate from each other, so that the mask essence carried by the seaweed cuprammonia non-woven fabric can act on the human facial skin more evenly, showing better application effect.

[0009] Preferably, the weight ratio of the modified seaweed fiber to the modified cuprammonium fiber is 2:8.

[0010] By adopting the above technical scheme, the modified seaweed fiber and modified cuprammonia fiber in the above weight ratio can form a relatively stable structure during the application and bonding process, so that the interface bonding stability between the modified seaweed fiber and the modified cuprammonia fiber is better, thereby obtaining a seaweed cuprammonia non-woven fabric with better tensile resistance.

[0011] Preferably, the modified seaweed fiber is prepared by the following steps: S1, soaking the seaweed fiber in an 8% calcium chloride solution, adding a 7% glutaraldehyde solution for cross-linking, the cross-linking temperature is 35° C., the time is 3 hours, taking out the seaweed fiber, washing and drying it, to obtain the pretreated seaweed fiber; S2. Acid hydrolyze microcrystalline cellulose in deionized water to obtain a cellulose nanocrystal solution with a mass fraction of 5%, and immerse the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treat at 30° C. for 50 minutes, then take out, wash with water and dry to obtain modified seaweed fiber.

[0012] By adopting the above technical scheme, in the preparation of modified seaweed fiber, the selection of the above parameters can enable the raw materials used in each step to exert better effects, thereby obtaining modified seaweed fiber with better application quality, and making the seaweed copper-ammonia non-woven fabric have better anti-tensile properties.

[0013] Preferably, the modified cuprammonia fiber is prepared by the following steps: S1, placing the cuprammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 7.5 MPa, and treating it for 4 min to obtain pretreated cuprammonia fiber; S2. Soak the pretreated cuprammonia fiber obtained in step S1 in a 50 mg / ml silk fibroin solution for 2 hours, take it out and dry it to obtain modified cuprammonia fiber.

[0014] By adopting the above technical scheme, in the preparation of modified cuprammonia fiber, the selection of the above parameters can enable the raw materials used in each step to exert better effects, thereby obtaining modified cuprammonia fiber with better application quality, and making the seaweed cuprammonia non-woven fabric have better anti-tear properties.

[0015] Preferably, in the preparation of the modified seaweed fiber, the weight ratio of the pretreated seaweed fiber to the cellulose nanocrystal solution is 1:(30-50).

[0016] By adopting the above technical scheme, the pretreated seaweed fiber and cellulose nanocrystal solution in the above weight ratio can fully act in the modification process. At this time, the fiber cross-section of the modified seaweed fiber presents an obvious serrated structure, and the serrated structure is uneven, which is more suitable for entanglement between fibers and interface bonding with the modified cuprammonia fiber, so that the finally obtained seaweed cuprammonia non-woven fabric exhibits better tensile resistance.

[0017] Preferably, in the preparation of the modified cuprammonia fiber, the ratio of the pretreated cuprammonia fiber to the silk fibroin solution is 1:(15-20).

[0018] By adopting the above technical scheme, the pretreated cuprammonia fiber and silk fibroin solution in the above weight ratio can fully act in the modification process. At this time, the special morphology and molecular structure of the modified cuprammonia fiber surface can show better interfacial adhesion, and can form a mosaic structure with the modified seaweed fiber with a serrated fiber cross-section structure, so that the final seaweed cuprammonia non-woven fabric exhibits better tensile resistance.

[0019] In a second aspect, the present application provides a method for preparing a seaweed copper-ammonia non-woven fabric, using the following technical solution: A method for preparing a seaweed copper-ammonia nonwoven fabric comprises the following steps: (1) combing the modified seaweed fiber to obtain a modified seaweed fiber web, and combing the modified cuprammonia fiber to obtain a modified cuprammonia fiber web; (2) laying the modified seaweed fiber web and the modified cuprammonia fiber web together to obtain a composite fiber web, and performing a hydroentanglement treatment to obtain a semi-finished product; (3) drying the semi-finished web, hot rolling and shaping, and obtaining the seaweed copper-ammonia non-woven fabric.

[0020] By adopting the above technical scheme, the above preparation steps are simple to operate, and the hydroentanglement treatment can make the modified seaweed fiber and the modified cuprammonia fiber tightly entangled and embraced together, thereby finally obtaining a seaweed cuprammonia non-woven fabric with excellent and stable quality.

[0021] Preferably, in step (3), the hot rolling setting temperature is 100-120° C., the hot rolling setting pressure is 0.05-0.1 MPa, and the time is 3-5 min.

[0022] By adopting the above technical scheme, during the hot rolling and shaping process, the above parameter control can enable the modified seaweed fiber and the modified cuprammonia fiber to form a relatively excellent and stable interface bonding state after entanglement, and it is not easy to slip and dislocate when subjected to pulling, thereby ensuring that the final seaweed cuprammonia non-woven fabric has excellent stability during the application process.

[0023] In summary, this application has the following beneficial effects: The modified seaweed fiber and modified cuprammonia fiber specially prepared in the present application can show better interface bonding strength between each other, and the structural strength of the fiber itself is also greatly improved, so that it is not easy to separate and dislocate when pulled, so that the seaweed cuprammonia non-woven fabric shows stable and better application effect, and the mask essence carried can act on the human facial skin more evenly, ensuring the overall use effect of the mask product. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0025] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available.

[0026] Seaweed fiber was purchased from Qingdao Hailan Biological Products Co., Ltd., item number hzd0001; Cuprammonia fiber Cuprammonia uses short-cut fibers, which are 1.4dtex*38mm cuprammonia fibers provided by Hangzhou Youbiao Textile Co., Ltd.

[0027] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified seaweed fiber is prepared by the following steps: S1, soaking the seaweed fiber in 20 times the weight of 8% calcium chloride solution, adding 5% by volume and 7% glutaraldehyde solution for cross-linking, the cross-linking temperature is 35° C., the time is 3 hours, taking out the seaweed fiber, washing and drying it, to obtain the pretreated seaweed fiber; S2. Acid hydrolyze microcrystalline cellulose in deionized water to obtain a cellulose nanocrystal solution with a mass fraction of 5%, and immerse the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treat at 30° C. for 50 minutes, then take out, wash with water and dry to obtain modified seaweed fiber.

[0028] Note: In step S2, concentrated sulfuric acid is used for acid hydrolysis for 100 min; the weight ratio of pretreated seaweed fiber to cellulose nanocrystal solution is 1:40.

[0029] Preparation Example 2 A modified seaweed fiber, which is different from Preparation Example 1 in that it is prepared by the following steps: S1, soaking the seaweed fiber in 20 times the weight of 7.5% calcium chloride solution, adding 5% by volume and 7% glutaraldehyde solution for cross-linking, the cross-linking temperature is 40° C., the time is 3 hours, taking out the seaweed fiber, washing and drying it, to obtain the pretreated seaweed fiber; S2. Acid hydrolyze microcrystalline cellulose in deionized water to obtain a cellulose nanocrystal solution with a mass fraction of 3.5%, and immerse the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treat at 25° C. for 50 min, then take out, wash with water, and dry to obtain modified seaweed fiber.

[0030] Preparation Example 3 A modified seaweed fiber, which is different from Preparation Example 1 in that it is prepared by the following steps: S1, soaking the seaweed fiber in 20 times the weight of 5% calcium chloride solution, adding 5% by volume and 6% glutaraldehyde solution for cross-linking, the cross-linking temperature is 30° C., the time is 4 hours, taking out the seaweed fiber, washing and drying it, to obtain the pretreated seaweed fiber; S2. Acid hydrolyze microcrystalline cellulose in deionized water to obtain a cellulose nanocrystal solution with a mass fraction of 2%, and immerse the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treat it at 20° C. for 60 minutes, then take it out, wash it with water and dry it to obtain modified seaweed fiber.

[0031] Preparation Example 4 A modified seaweed fiber, which is different from Preparation Example 1 in that it is prepared by the following steps: S1, soaking the seaweed fiber in 20 times the weight of 10% calcium chloride solution, adding 5% by volume and 8% glutaraldehyde solution for cross-linking, the cross-linking temperature is 50° C., the time is 2 hours, taking out the seaweed fiber, washing and drying it, to obtain the pretreated seaweed fiber; S2, placing microcrystalline cellulose in deionized water for acid hydrolysis to obtain a cellulose nanocrystal solution with a mass fraction of 5%, soaking the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treating at 30° C. for 40 minutes, then taking out, washing with water and drying to obtain modified seaweed fiber.

[0032] Preparation Example 5 A modified seaweed fiber, which is different from Preparation Example 1 in that the weight ratio of the pretreated seaweed fiber to the cellulose nanocrystal solution is 1:30.

[0033] Preparation Example 6 A modified seaweed fiber, which is different from Preparation Example 1 in that the weight ratio of the pretreated seaweed fiber to the cellulose nanocrystal solution is 1:50.

[0034] Preparation Example 7 A modified cuprammonia fiber is prepared by the following steps: S1, placing the cuprammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 7.5 MPa, and treating it for 4 min to obtain pretreated cuprammonia fiber; S2. Soak the pretreated cuprammonia fiber obtained in step S1 in a 50 mg / ml silk fibroin solution for 2 hours, take it out and dry it to obtain modified cuprammonia fiber.

[0035] Note: In step S2, the ratio of pretreated cuprammonium fiber to silk fibroin solution is 1:17.5.

[0036] Preparation Example 8 A modified cuprammonia fiber, which is different from Preparation Example 7 in that it is prepared by the following steps: S1, placing the cuprammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 7Mpa, and treating it for 5min to obtain pretreated cuprammonia fiber; S2. Soak the pretreated cuprammonia fiber obtained in step S1 in a 45 mg / ml silk fibroin solution for 3 hours, take it out and dry it to obtain modified cuprammonia fiber.

[0037] Preparation Example 9 A modified cuprammonia fiber, which is different from Preparation Example 7 in that it is prepared by the following steps: S1, placing the copper ammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 8Mpa, and treating it for 3min to obtain pretreated copper ammonia fiber; S2. Soak the pretreated cuprammonia fiber obtained in step S1 in a 55 mg / ml silk fibroin solution for 1 hour, take it out and dry it to obtain modified cuprammonia fiber.

[0038] Preparation Example 10 A modified cuprammonia fiber, which is different from Preparation Example 7 in that the amount ratio of the pretreated cuprammonia fiber to the silk fibroin solution is 1:15.

[0039] Preparation Example 11 A modified cuprammonia fiber, which is different from Preparation Example 7 in that the amount ratio of the pretreated cuprammonia fiber to the silk fibroin solution is 1:20. Example

[0040] Example 1 A seaweed copper-ammonia nonwoven fabric, the raw materials used and their corresponding weight parts are shown in Table 1, and the fabric is prepared by the following method: (1) combing modified seaweed fiber to obtain a modified seaweed fiber web, and combing modified copper-ammonia fiber to obtain a modified copper-ammonia fiber web; (2) laying the modified seaweed fiber web and the modified copper-ammonia fiber web together to obtain a composite fiber web, and performing a hydroentanglement treatment to obtain a semi-finished product; (3) drying the semi-finished web, hot rolling and shaping, and obtaining the seaweed copper-ammonia non-woven fabric.

[0041] Note: In the above operation, the modified seaweed fiber is obtained in Preparation Example 1, and the modified cuprammonium fiber is obtained in Preparation Example 7; the hydroentanglement treatment in step (2) includes drum hydroentanglement, drum hydroentanglement, flat net hydroentanglement, drum hydroentanglement, and flat net hydroentanglement in sequence, and the pressures of the five hydroentanglement treatments (hydroentanglement pressures) are 0.7 MPa, 5 MPa, 9 MPa, 11 MPa, and 15 MPa, respectively; in step (3), the hot rolling setting temperature is 110°C, the hot rolling setting pressure is 0.07 MPa, and the time is 4 min.

[0042] Example 2-3 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the raw materials used and their corresponding weight parts are as shown in Table 1.

[0043] Table 1 Raw materials and their weight parts in Example 13 (kg / part) raw material Example 1 Example 2 Example 3 Modified seaweed fiber 21.5 18 25 Modified cuprammonia fiber 80 75 85 Example 4 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified seaweed fiber is obtained in Preparation Example 2.

[0044] Example 5 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified seaweed fiber is obtained in Preparation Example 3.

[0045] Example 6 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified seaweed fiber is obtained in Preparation Example 4.

[0046] Example 7 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified seaweed fiber is obtained in Preparation Example 5.

[0047] Example 8 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified seaweed fiber is obtained in Preparation Example 6.

[0048] Example 9 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified copper-ammonia fiber is obtained in Preparation Example 8.

[0049] Example 10 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified copper-ammonia fiber is obtained in Preparation Example 9.

[0050] Embodiment 11 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified copper-ammonia fiber is obtained in Preparation Example 10.

[0051] Example 12 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified copper-ammonia fiber is obtained in Preparation Example 11.

[0052] Embodiment 13 A seaweed-copper-ammonia nonwoven fabric is different from Example 1 in that the total amount of modified seaweed fiber and modified cuprammonia fiber remains unchanged, and the weight ratio of the two is adjusted to 2:8.

[0053] Embodiment 14 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that, in step (3), the hot rolling setting temperature is 100° C., the hot rolling setting pressure is 0.05 MPa, and the time is 5 minutes.

[0054] Embodiment 15 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that, in step (3), the hot rolling setting temperature is 120° C., the hot rolling setting pressure is 0.1 MPa, and the time is 3 minutes.

[0055] Comparative Example Comparative Example 1 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified seaweed fiber is replaced with unmodified seaweed fiber raw material.

[0056] Comparative Example 2 A seaweed copper-ammonia non-woven fabric, which is different from Example 1 in that the modified copper-ammonia fiber is replaced with the copper-ammonia fiber raw material before modification.

[0057] Comparative Example 3 A seaweed copper-ammonia nonwoven fabric, which is different from Example 1 in that the modified seaweed fiber is replaced by the unmodified seaweed fiber raw material, and the modified copper-ammonia fiber is replaced by the unmodified copper-ammonia fiber raw material.

[0058] Performance test test samples: The seaweed copper-ammonia nonwoven fabrics obtained in Examples 1-15 were used as test samples 1-15, and the seaweed copper-ammonia nonwoven fabrics obtained in Comparative Examples 1-3 were used as control samples 1-3.

[0059] Test method: (1) Use POROLUX100 (Gas-Liquid Encryption Pore Size Tester-A) 03030833 Star Capillary Flow Pore Size Analyzer to test the seaweed copper-ammonia non-woven fabric to obtain the average pore size; (2) The porosity of the seaweed copper-ammonia nonwoven fabric was calculated and tested, and the calculation formula was as follows: n = 1-m / ρδ; where n is the porosity, %; ρ is the average fiber density, g / m 3 ; δ is the material thickness, mm; m is the material surface density, g / m 2 ; (3) Take test samples 1-15 and control samples 1-3, and perform the tests of (1) and (2) above, and the initial average pore size obtained is recorded as A1 and the initial porosity is recorded as B1 respectively; at the same time, cut the test samples 1-15 and the control samples 1-3 into samples with a length of 300 mm and a width of 50 mm, and then use a YG028 universal material testing machine to apply a tensile force of 120 Newtons in the horizontal and longitudinal directions for 20 seconds, and then use the tests of (1) and (2) above, and the average pore size after pulling is recorded as A2 and the porosity after pulling is recorded as B2 respectively; then calculate the average pore size change rate and porosity change rate, the average pore size change rate = (A2-A1) / A1, the porosity change rate = (B2-B1) / B1, the larger the change rate, the worse the tensile resistance of the seaweed copper-ammonia non-woven fabric.

[0060] Table 2 Test results of test samples 1-15 and control samples 1-3 sample Average pore size change rate (%) Porosity change rate (%) Test sample 1 4.16 5.41 Test sample 2 4.32 5.55 Test sample 3 4.25 5.48 Test sample 4 4.21 5.45 Test sample 5 4.27 5.49 Test sample 6 4.30 5.52 Test sample 7 4.23 5.47 Test sample 8 4.18 5.44 Test sample 9 4.20 5.46 Test sample 10 4.24 5.51 Test sample 11 4.26 5.53 Test sample 12 4.19 5.43 Test sample 13 3.92 5.26 Test sample 14 4.18 5.50 Test sample 15 4.22 5.52 Control sample 1 9.81 11.24 Control sample 2 9.18 10.85 Control sample 3 12.56 14.78 Combining Examples 1-3 and Comparative Examples 1-3 and Table 2, it can be seen that the modified seaweed fiber and the modified cuprammonia fiber can show better interfacial bonding strength with each other, and are not easy to separate and dislocate when dealing with pulling, so that the average pore size change rate and porosity change rate obtained by the seaweed cuprammonia non-woven fabric test are significantly lower; the anti-pulling performance shown by the combination of ordinary seaweed fiber raw materials and ordinary cuprammonia fiber raw materials is significantly poor. If the modified seaweed fiber and ordinary cuprammonia fiber raw materials are matched, or the modified cuprammonia fiber and ordinary seaweed fiber raw materials are used, the effect is improved to a certain extent, but it is extremely limited, and is far less than the excellent improvement effect brought by the combination of modified seaweed fiber and modified cuprammonia fiber. Combining Example 13 and Table 2, it can be seen that when the weight ratio of modified seaweed fiber and modified cuprammonia fiber is 2:8, the interfacial bonding stability of the two is better, and then a seaweed cuprammonia non-woven fabric with better anti-pulling performance is obtained.

[0061] It can be seen from Example 1, Example 4-12 and Table 2 that the modified seaweed fiber and modified cuprammonia fiber obtained by the special method of the present application can show a stable and better matching effect during the application process, so that the obtained seaweed cuprammonia non-woven fabric has excellent anti-pulling performance, thereby ensuring that the mask essence material carried by it can act on the human facial skin more evenly. In the preparation of the modified seaweed fiber, the weight ratio of the pretreated seaweed fiber to the cellulose nanocrystal solution is 1: (30-50), and in the preparation of the modified cuprammonia fiber, the amount ratio of the pretreated cuprammonia fiber to the silk protein solution is 1: (15-20), which can make the final seaweed cuprammonia non-woven fabric show better anti-pulling performance.

[0062] It can be seen from Example 1, Examples 14-15 and Table 2 that in step (3), the hot rolling temperature is 100-120°C, the hot rolling pressure is 0.05-0.1MPa, and the time is 3-5min, which can enable the modified seaweed fiber and the modified cuprammonia fiber to form a relatively excellent and stable interface bonding state after entanglement, and the average pore size change rate and porosity change rate are both low and stable.

[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A seaweed copper-ammonia nonwoven fabric, characterized in that: Made from the following raw materials in parts by weight: 18-25 parts of modified seaweed fiber; 75-85 parts of modified cuprammonia fiber; The modified seaweed fiber is prepared by the following steps: S1, soaking the seaweed fiber in a 5-10% calcium chloride solution, adding a 6-8% glutaraldehyde solution for cross-linking, the cross-linking temperature is 30-50° C., the time is 2-4 hours, taking out the seaweed fiber, washing and drying it, to obtain the pretreated seaweed fiber; S2, placing microcrystalline cellulose in deionized water for acid hydrolysis to obtain a cellulose nanocrystal solution with a mass fraction of 2-5%, soaking the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treating at 20-30° C. for 40-60 min, then taking out, washing with water and drying to obtain modified seaweed fiber; The modified cuprammonia fiber is prepared by the following steps: S1, placing the copper ammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 7-8Mpa, and treating it for 3-5min to obtain pretreated copper ammonia fiber; S2. Soak the pretreated cuprammonium fiber obtained in step S1 in a silk fibroin solution with a concentration of 45-55 mg / ml for 1-3 hours, take it out and dry it to obtain modified cuprammonium fiber.

2. The seaweed copper-ammonia nonwoven fabric according to claim 1, characterized in that: The weight ratio of the modified seaweed fiber to the modified cuprammonia fiber is 2:

8.

3. The seaweed copper-ammonia nonwoven fabric according to claim 1, characterized in that: The modified seaweed fiber is prepared by the following steps: S1, soaking the seaweed fiber in 8% calcium chloride solution, adding 7% glutaraldehyde solution for cross-linking, the cross-linking temperature is 35° C., the time is 3 h, taking out the seaweed fiber, washing and drying it, to obtain pretreated seaweed fiber; S2. Acid hydrolyze microcrystalline cellulose in deionized water to obtain a cellulose nanocrystal solution with a mass fraction of 5%. Immerse the pretreated seaweed fiber obtained in step S1 in the cellulose nanocrystal solution, treat at 30° C. for 50 min, then take out, wash and dry to obtain modified seaweed fiber.

4. The seaweed copper-ammonia nonwoven fabric according to claim 1, characterized in that: The modified cuprammonia fiber is prepared by the following steps: S1, placing the cuprammonia fiber in a pressure vessel, filling it with carbon dioxide medium, controlling the pressure to 7.5 MPa, and treating it for 4 min to obtain pretreated cuprammonia fiber; S2. Soak the pretreated cuprammonia fiber obtained in step S1 in a 50 mg / ml silk fibroin solution for 2 hours, take it out and dry it to obtain modified cuprammonia fiber.

5. The seaweed copper-ammonia nonwoven fabric according to claim 1, characterized in that: In the preparation of the modified seaweed fiber, the weight ratio of the pretreated seaweed fiber to the cellulose nanocrystal solution is 1:(30-50).

6. The seaweed copper-ammonia nonwoven fabric according to claim 1, characterized in that: In the preparation of the modified cuprammonia fiber, the amount ratio of the pretreated cuprammonia fiber to the silk fibroin solution is 1:(15-20).

7. The method for preparing the seaweed copper-ammonia nonwoven fabric according to claim 1, characterized in that: The following steps are involved: (1) combing the modified seaweed fiber to obtain a modified seaweed fiber web, and combing the modified cuprammonia fiber to obtain a modified cuprammonia fiber web; (2) Laying the modified seaweed fiber web and the modified cuprammonium fiber web together to obtain a composite fiber web, and performing a hydroentanglement treatment to obtain a semi-finished product; (3) Drying the semi-finished web, hot rolling and shaping, and obtaining the seaweed copper-ammonia non-woven fabric.

8. The method for preparing the seaweed copper-ammonia nonwoven fabric according to claim 7, characterized in that: In step (3), the hot rolling setting temperature is 100-120°C, the hot rolling setting pressure is 0.05-0.1MPa, and the time is 3-5min.

Citation Information

Patent Citations

  • Alginate fiber spunlace non-woven fabric and manufacturing method thereof

    CN105401337A

  • Bio-cellulose mask base fabric and bio-cellulose mask

    CN107217485A

  • Kapok and copper ammonia fiber blended mask cloth and production method thereof

    CN112593342A

  • Chitosan quaternary ammonium salt / seaweed composite antibacterial fiber, preparation method thereof and application of chitosan quaternary ammonium salt / seaweed composite antibacterial fiber in home textile products for children

    CN112921449A

  • Gel mask and preparation method thereof

    CN115869211A